Análisis de las sanciones que cometen los contadores públicos en el marco de su desarrollo como ejercicio profesional (2023)
This research work is a descriptive analysis of the behavior of Certified Public Accountants accredited by the Central Board of Accountants during the last three years, The main objective of the research is to analyze the reasons why the Central Board of Accountants performs sanctions to accounting professionals and describes infractions in which are frequently incurred.